Perceptual latency priming: A measure of attentional facilitation. - Scharlau, Ingrid (Psychological Research)
The present paper reviews recent research on perceptual latency priming (PLP). PLP is the relative latency advantage--earlier perception--of a visual stimulus that is preceded by another, masked stimulus at its location. The first stimulus attracts attention which accelerates perception of the second stimulus. This facilitation arises even if the first stimulus is visually backward-masked by the second one. The paper summarises research on temporal and spatial properties of PLP and the question whether intentions mediate shifts of attention to external events. Possible sources of PLP besides visuo-spatial attention are discussed. Finally, I give a review of feedforward and reentrant models of PLP and compare them to the empirical evidence. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; attentional facilitation; visuospatial attention; visual backward masking; prior entry; Attention; Humans; Judgment; Reaction Time; Space Perception; Attention; Priming; Response Latency; Visual Masking; Visuospatial Ability

Evidence for split foci of attention in a priming paradigm. - Scharlau, Ingrid (Perception & Psychophysics)
Most models of visuospatial attention include the notion that attention is dedicated to a single location in space. However, several researchers have found evidence that under appropriate circumstances, attention may be allocated to noncontiguous locations (e.g., Awn & Pashler, 2000; Bichot, Cave, & Pashler, 1999; Kramer & Hahn, 1995). In the present experiments, the spatial distribution of attention was assessed by a novel method, perceptual latency priming: the latency benefit of an attended visual stimulus, as compared with a nonattended stimulus. Experiment 1 assessed whether observers are able to attend to two nonadjacent regions or a region of variable size. Experiment 2 tested whether, when two distant locations are attended to, the region between them is necessarily also in the focus of attention. Two further experiments controlled for objections against the method used and replicated the main results of the first two experiments. The experiments showed a robust attentional pr
Keywords: visuospatial attention; priming paradigm; spatial distribution; Adult; Attention; Female; Humans; Male; Attention; Priming; Spatial Perception; Visuospatial Ability